A healthcare management system for Turkey based on a service-oriented architecture - GÜRDER, FİLİZ (TAYLOR & FRANCIS INC, 2013)
The current Turkish healthcare management system has a structure that is extremely inordinate, cumbersome and inflexible. Furthermore, this structure has no common point of view and thus has no interoperability and responds slowly to innovations. The purpose of this study is to show that using which methods can the Turkish healthcare management system provide a structure that could be more modern, more flexible and more quick to respond to innovations and changes taking advantage of the benefits given by a service-oriented architecture (SOA). In this paper, the Turkish healthcare management system is chosen to be examined since Turkey is considered as one of the Third World countries and the information architecture of the existing healthcare management system of Turkey has not yet been configured with SOA, which is a contemporary innovative approach and should provide the base architecture of the new solution. The innovation of this study is the symbiosis of two main integration approaches, SOA and Health Level 7 (HL7), for integrating divergent healthcare information systems. A model is developed which is based on SOA and enables obtaining a healthcare management system having the SSF standards (HSSP Service Specification Framework) developed by the framework of the HSSP (Healthcare Services Specification Project) under the leadership of HL7 and the Object Management Group.
Keywords: Healthcare services; HSSP (Healthcare Services Specification Project); SSF (HSSP Service Specification Framework); design principles; interoperability; healthcare legacy systems integration; INFORMATION-SYSTEMS